1993
DOI: 10.1083/jcb.122.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Maximal migration of human smooth muscle cells on fibronectin and type IV collagen occurs at an intermediate attachment strength

Abstract: Abstract. Although a biphasic dependence of cell migration speed on cell-substratum adhesiveness has been predicted theoretically, experimental data directly demonstrating a relationship between these two phenomena have been lacking. To determine whether an optimal strength of cell-substratum adhesive interactions exists for cell migration, we measured quantitatively both the initial attachment strength and migration speed of human smooth muscle cells (HSMCs) on a range of surface concentrations of fibronectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
444
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(512 citation statements)
references
References 33 publications
62
444
6
Order By: Relevance
“…Our findings suggest that the role of Sema3A in GBM migration/dispersal is complex and perhaps biphasic. There is a biphasic relationship between the adhesive strength and cell motility of cells such that there is optimal adhesion for maximal cell motility (DiMilla et al, 1993;Cox and Huttenlocher, 1998). Similarly, our findings are consistent with an optimal Sema3A concentration for GBM dispersal such that GBM cells are able to release their adhesions efficiently and move away from one another.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings suggest that the role of Sema3A in GBM migration/dispersal is complex and perhaps biphasic. There is a biphasic relationship between the adhesive strength and cell motility of cells such that there is optimal adhesion for maximal cell motility (DiMilla et al, 1993;Cox and Huttenlocher, 1998). Similarly, our findings are consistent with an optimal Sema3A concentration for GBM dispersal such that GBM cells are able to release their adhesions efficiently and move away from one another.…”
Section: Discussionsupporting
confidence: 87%
“…Cell migratory ability can be also determined by the absolute concentrations of ECM components: this mechanism is called haptokinesis. At this regard, several experimental studies show that cell speed, spreading, and membrane activity is maximal at intermediate levels of ECM densities, both on 2D substrates [14,19] and in 3D matrices [73]. Also the local rigidity of the matrix plays a fundamental role in determining the efficiency and the direction of cell crawling, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although this work did not determine whether the MMP-1 was bound to the ␣ 2 ␤ 1 or ␣ 1 ␤ 1 integrins, the finding is entirely consistent with the model we have presented in this report. Indeed, it has been shown that an intermediate level of integrin expression is required for optimal migration (43). If levels are too low, the cell cannot gain traction; if levels are too high, presumably the cell becomes too firmly attached to the matrix.…”
Section: Figmentioning
confidence: 99%